Nuclear receptor interaction protein, a coactivator of androgen receptors (AR), is regulated by AR and Sp1 to feed forward and activate its own gene expression through AR protein stability - Chen, Pei-Hong; Tsao, Yeou-Ping; Wang, Chih-Chiang; Chen, Show-Li (Nucleic acids research, 2008)
Previously, we found a novel gene, nuclear receptor interaction protein (NRIP), a transcription cofactor that can enhance an AR-driven PSA promoter activity in a ligand-dependent manner in prostate cancer cells. Here, we investigated NRIP regulation. We cloned a 413-bp fragment from the transcription initiation site of the NRIP gene that had strong promoter activity, was TATA-less and GC-rich, and, based on DNA sequences, contained one androgen response element (ARE) and three Sp1-binding sites (Sp1-1, Sp1-2, Sp1-3). Transient promoter luciferase assays, chromatin immunoprecipitation and small RNA interference analyses mapped ARE and Sp1-2-binding sites involved in NRIP promoter activation, implying that NRIP is a target gene for AR or Sp1. AR associates with the NRIP promoter through ARE and indirectly through Sp1-binding site via AR-Sp1 complex formation. Thus both ARE and Sp1-binding site within the NRIP promoter can respond to androgen induction. More intriguingly, NRIP plays a feed-forward role enhancing AR-driven NRIP promoter activity via NRIP forming a complex with AR to protect AR protein from proteasome degradation. This is the first demonstration that NRIP is a novel AR-target gene and that NRIP expression feeds forward and activates its own expression through AR protein stability.